Unlocking Entrepreneurship in the FinTech Era: The Role of Tax Compliance in Business Performance - Konstantinos S. Skandalis; Dimitra Skandali (FinTech)
This study examines the effect of FinTech on entrepreneurial performance and the essentiality of tax compliance and entrepreneurial orientation. Drawing on information from small and medium enterprises (SMEs) in Greece and utilizing Structural Equation Modeling techniques, our study shows that FinTech plays a key role in improving tax adherence and entrepreneurial mindsets, which subsequently enhances entrepreneurial success. FinTech promotes greater transparency, easier reporting, and less compliance burdens. Companies that make use of FinTech tools see enhancements in meeting tax regulation requirements efficiently and effectively without being weighed down by compliance issues that take up resources meant for innovation and strategic development instead. Moreover, this research highlights the impact of incorporating financial technology solutions for improved management and cultivating an innovative and forward-thinking environment. It highlights the importance of implementing strategies to boost FinTech adoption and foster entrepreneurial achievements, effectively sliding tax compliance into focus. Our research identifies the revolutionary impact of FinTech tools and sheds light on how technological progress can fuel entrepreneurship and improve business outcomes overall.